2022
DOI: 10.1007/s11442-022-2009-2
|View full text |Cite
|
Sign up to set email alerts
|

Bank and point bar morphodynamics in the Lower Jingjiang Reach of the Yangtze River in response to the Three Gorges Project

Abstract: Geomorphic dynamics of alluvial rivers in response to upstream damming have substantial impacts on navigation, habitat protection, and channel stability. The purpose of this study was to determine how flow and sediment regimes, and meander characteristics affect the morphological adjustment of bends in the Lower Jingjiang Reach (LJR) before and after the Three Gorges Project (TGP). Based on detailed field measurements and hydrological and topographic datasets from 1991 to 2016, banks and point bars morphodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Therefore, the implementation of bank revetment works should not be the major cause for the changes in deformation pattern. Previous studies indicated that the discharge ratio between the main stem (Yangtze River) and tributary (Dongting Lake) did not changed significantly and the water stage also remained relatively stable at the confluence after upstream damming (Feng et al., 2013). Besides, the morphodynamics of TG bend is not influenced by backwater effect induced by the Dongting Lake, but the morphological changes of TG bend were similar to the QGL and GYZ bends (H. Y. Wang et al., 2022). Therefore, the confluence of the Dongting Lake should not be a critical influencing factor. The hydrological regime changed significantly in the MYR after the TGP operation (Figure 2b).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Therefore, the implementation of bank revetment works should not be the major cause for the changes in deformation pattern. Previous studies indicated that the discharge ratio between the main stem (Yangtze River) and tributary (Dongting Lake) did not changed significantly and the water stage also remained relatively stable at the confluence after upstream damming (Feng et al., 2013). Besides, the morphodynamics of TG bend is not influenced by backwater effect induced by the Dongting Lake, but the morphological changes of TG bend were similar to the QGL and GYZ bends (H. Y. Wang et al., 2022). Therefore, the confluence of the Dongting Lake should not be a critical influencing factor. The hydrological regime changed significantly in the MYR after the TGP operation (Figure 2b).…”
Section: Discussionmentioning
confidence: 88%
“…H. Y. Wang et al. (2022) investigated the channel evolution around the QGL and GYZ bends during the pre‐damming period and found that the point bars attached to the inner banks remained relatively stable, with the area of point bars in the QGL bend increasing by 3% and the GYZ bend decreasing by 10% during the period 1996–2002, and the longitudinal benches did not form along the outer banks. However, the point bar attached to the inner bank was removed upstream of the bend apex in 2018, and the thalweg shifted from the outer bank toward the inner bank substantially (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations